THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON SMARTPHONE PURCHASE DECISIONS APPLE CASE STUDY ON MILLENNIALS IN KOTABUMI TANGERANG - Tarto, Tarto; Soenjaya, Teddy Jonathan; Sumarga, Hendi Eka (Dynamic Management Journal, 2025)
This research is motivated by the phenomenon of smartphone development, where competition between companies is getting tighter on smartphones. Apple is a company engaged in hardware and software, including Apple's hardware is the Iphone. Apple proved to be one of the big companies, it came from Apple's global sales reaching 150 million units, but in Indonesia according to TBI from 2011 to 2013 the percentage was only able to control less than 5%. The purpose of this study is to determine the influence of brand image and product quality on the purchase of a decision iPhone. This type of research is explanatory research, with data collection through questionnaires, literature studies, and interviews. The sampling technique uses the census technique using a questionnaire of research instruments. The sample in this study amounted to 58 respondents who were iPhone users in S1 FISIP Diponegoro University students. This study uses linear regression analysis techniques and significance tests are used to prove the hypothesis using SPSS for windows version 20.0. The results show that brand image (X1), and product quality (X2), both jointly and individually, have a positive effect on the purchase decision of the dependent variable (Y). Simultaneously, brand image, product quality, affects purchasing decisions by 40.7% according to multiple regression.